193k views
3 votes
Find ( f + g)(x).

f (x) = -5x2 - 3x + 2 and g(x) = 2x2 + 5x - 1

User Zdimension
by
5.0k points

1 Answer

3 votes

Answer:


\large\boxed{(f+g)(x)=-3x^2+2x+1}

Explanation:


f(x+y)=f(x)+g(x)\\\\f(x)=-5x^2-3x+2,\ g(x)=2x^2+5x-1\\\\\text{Substitute:}\\\\(f+g)(x)=(-5x^2-3x+2)+(2x^2+5x-1)\\\\=-5x^2-3x+2+2x^2+5x-1\qquad\text{combine like terms}\\\\=(-5x^2+2x^2)+(-3x+5x)+(2-1)\\\\=-3x^2+2x+1

User Elisse
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.